Invasive Suckermouth Catfishes (Siluriformes, Loricariidae) in Bangladesh Wetlands: Present Status and Challenges (Bangladesh Journal of Zoology, 2024)
The suckermouth catfish (SMF) is an invasive species in Bangladesh that has had a huge negative impact on ecosystems including rivers, lakes and wetlands. Several SMFs had been introduced as aquarium fish in the early 80’s. The first report of this fish in Bangladesh was recorded in 2008; more recently, it has been banned in September 2022 due to its alarming adverse impact on flora and fauna of inland waterbodies. This review explores the complex ecological, economic, and social dynamics triggered by several species of SMFs. The information on SMF’s rapid proliferation, adaptability, and destructive capacity on inland waterbodies were underscored, as well as the resulting challenges significant to the indigenous aquatic flora and fauna, habitats, and livelihoods of the wetland-dependent communities. However, the eradication of SMFs from inland waterbodies would be a major challenge. Moreover, a cautious yet prospective plan for either exploitation or eradication, along with inflexible ecological safeguards, are recommended. Technological supports such as environmental DNA (eDNA) techniques, together with the integration of image processing, machine learning, and robotics, may be favorably used in detecting the presence of SMFs. Additionally, identifying habitat, distribution, and hotspot should be considered for needful action. This review highlights a multifaceted narrative of SMF in Bangladesh, emphasizing a complex balance between ecological conservation, economic gains, and technological innovations. Therefore, the illustrated information of SMFs could be helpful to enhance the current knowledges which may lead our nation towards ecological resilience and sustainable harmony against future aquatic invasions. This review suggests advanced action plan and collaboration among different fisheries stakeholders, government authorities and policy makers for eradication or sustainable management of SMFs in inland waterbodies. Bangladesh J. Zool. 51(3): 371-396, 2023